Characteristics of enriched components from thermal dissolution extracts of Zhaotong lignite using solid phase microextraction. (15th April 2022) - Yan, Yang-Yang; Wang, Chu-Fan; Fan, Xing; Gao, Zhen-Yu; Wei, Wen-Han; Zhao, Guo-Ming; Liang, Peng; Hou, Ran-Ran; Wei, Xian-Yong
Highlights: Enrichment characteristics are probed from the molecular structure. Aliphatic hydrocarbons were selectively enriched by polydimethylsiloxane coating. Oxygenated aromatic species with multiple and/or long side chains were enriched. Abstract: Due to the low concentration of minor compounds and the detection limit of instruments, numerous compounds in the thermal dissolution (TD) extract of coals cannot be detected. Therefore, it is necessary to introduce solid phase microextraction (SPME) for sampling before analysis, which can enrich compounds in mixtures with similar molecular structures and exclude interferences from other components. In this work, partial species in the TD extract of Zhaotong lignite were enriched by SPME with a polydimethylsiloxane (PDMS) coating. The enrichment characteristics of the coating on TD extract were examined by gas chromatography-mass spectrometry (GC–MS). Nitrogen-containing compounds and sulfur-containing compounds were removed from the enriched species, and the content of aliphatic hydrocarbons increased from 30.0% to 93.2% after enrichment. Oxygenated aromatic compounds with structures similar to the long-chain siloxane bonds of PDMS were also enriched. This study establishes a SPME method and provides a basis for the analysis of lignite and its derivatives.